The role of quality of work life in enhancing the quality of decision-making “A survey study of the opinions of a sample of employees of the University of Sulaimani” - Afa Omar Fatah (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The aim of the research is to examine the effect of quality of work life dimensions on enhancing the quality of decision making at the University of Sulaimani. After reviewing previous studies on quality of work life and the quality of decision making, theoretical concepts were written and research questions were constructed. A questionnaire was designed to collect data and distributed to the respondents of (58) employees at the University of Sulaimani. A number of tests were carried out before and after the distribution of the questionnaire to verify its validity and reliability and to ascertain its validity in measuring the variables of the study such as consistency and test of data moderation. Several statistical methods were used to analyze the data and answer the hypotheses. The results showed statistically significant effect of the quality of work life in the quality of decision making variable. Based on the results of the research, a number of recommendations were presented as well as the proposed work of the university on a permanent basis to enable the employees to work independently and to apply their creative ideas, which reflect their positive returns on both the quality of work life and the quality of decision making through improving the basic skills and abilities of their human resources and giving them opportunities to participate in training courses.